2017
DOI: 10.1111/eth.12614
|View full text |Cite
|
Sign up to set email alerts
|

Low temperatures during ontogeny increase fluctuating asymmetry and reduce maternal aggression in the house mouse, Mus musculus

Abstract: Maternal aggression is behavior displayed by post-partum lactating female mice toward unfamiliar conspecifics, presumably as a defense against infanticide. A variety of perinatal stressors can impair maternal care in adulthood. Previous studies on associations between developmental perturbations and maternal aggression have produced mixed results. To address this issue, we employed a proxy for developmental instability, fluctuating asymmetry (FA) to further elucidate the relationship between low temperature st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…We chose cold stress as a physiologically relevant model since the hypothalamus plays a prominent role in thermoregulation (Bachtell et al, 2003;Kasahara et al, 2013;Laperrousaz et al, 2018) and cold exposure has been shown to elevate corticosterone levels and alter microglial physiology in adult mice (Xu et al, 2019). Moreover, cold exposure during the pre-and/or postnatal period can impact aggressive behaviors controlled by hypothalamic circuits (Benderlioglu and Dow, 2017;Hohmann et al, 2013), suggesting that cold stress can alter hypothalamic development and function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose cold stress as a physiologically relevant model since the hypothalamus plays a prominent role in thermoregulation (Bachtell et al, 2003;Kasahara et al, 2013;Laperrousaz et al, 2018) and cold exposure has been shown to elevate corticosterone levels and alter microglial physiology in adult mice (Xu et al, 2019). Moreover, cold exposure during the pre-and/or postnatal period can impact aggressive behaviors controlled by hypothalamic circuits (Benderlioglu and Dow, 2017;Hohmann et al, 2013), suggesting that cold stress can alter hypothalamic development and function.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothalamus is essential for maintaining homeostatic processes, such as fluid-balance, body temperature, energy regulation, metabolism, physical activity, diurnal activity, reproduction, parturition, and lactation (Berthoud, 2002;Hill et al, 2008;Li et al, 1998;Nesan and Kurrasch, 2016;van Dijk et al, 2011). Less appreciated but equally important, the hypothalamus also influences emotional outputs, such as aggression and defensiveness, as well as other social behaviors (Bandler et al, 2000;Benderlioglu and Dow, 2017;Hohmann et al, 2013). The release of trophic hormones, which serve to connect the nervous system to the peripheral endocrine system, enables the hypothalamus to regulate homeostasis, and this is especially true for stress (F€ uzesi et al, 2016;Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%